Efficacy and safety of certolizumab pegol plus methotrexate in active rheumatoid arthritis: the RAPID 2 study. A randomised controlled trial. Issue 6 (17th November 2008) - Smolen, J; Landewé, R B; Mease, P; Brzezicki, J; Mason, D; Luijtens, K; van Vollenhoven, R F; Kavanaugh, A; Schiff, M; Burmester, G R; Strand, V; Vencovský, J; et al.
Abstract : Background: Certolizumab pegol is a PEGylated tumour necrosis factor inhibitor. Objective: To evaluate the efficacy and safety of certolizumab pegol versus placebo, plus methotrexate (MTX), in patients with active rheumatoid arthritis (RA). Methods: An international, multicentre, phase 3, randomised, double-blind, placebo-controlled study in active adult-onset RA. Patients (n = 619) were randomised 2:2:1 to subcutaneous certolizumab pegol (liquid formulation) 400 mg at weeks 0, 2 and 4 followed by 200 mg or 400 mg plus MTX, or placebo plus MTX, every 2 weeks for 24 weeks. The primary end point was ACR20 response at week 24. Secondary end points included ACR50 and ACR70 responses, change from baseline in modified Total Sharp Score, ACR core set variables and physical function. Results: Significantly more patients in the certolizumab pegol 200 mg and 400 mg groups achieved an ACR20 response versus placebo (p⩽0.001); rates were 57.3%, 57.6% and 8.7%, respectively. Certolizumab pegol 200 and 400 mg also significantly inhibited radiographic progression; mean changes from baseline in mTSS at week 24 were 0.2 and −0.4, respectively, versus 1.2 for placebo (rank analysis p⩽0.01). Certolizumab pegol-treated patients reported rapid and significant improvements in physical function versus placebo; mean changes from baseline in HAQ-DI at week 24 were −0.50 and −0.50, respectively, versus −0.14 for placebo (p⩽0.001). Most adverse events were mild or moderate, with low incidence of withdrawals due to adverse events. Five patients developed tuberculosis. Conclusion: Certolizumab pegol plus MTX was more efficacious than placebo plus MTX, rapidly and significantly improving signs and symptoms of RA and physical function and inhibiting radiographic progression. Trial registration number: NCT00175877